MiR-19a regulates the cell growth and apoptosis of osteosarcoma stem cells by targeting PTEN. Issue 5 (April 2017) - Zhao, Di; Chen, Youbin; Chen, Shunliang; Zheng, Chuangyi; Hu, Jun; Luo, Shaowei
MicroRNAs are small, endogenous, and non-coding RNAs that play important regulatory roles in multiple biological processes in cancers. Recent evidence has indicated that miR-19a participates in the cancer tumorigenic progression. However, the functional roles of miR-19a in cancer stem cells are still unclear. As the cancer stem cells are considered to be responsible for the tumor recurrence and treatment failure in osteosarcoma, the aim of this study is to investigate the molecular mechanism of miR-19a underlying osteosarcoma tumorigenesis. In this study, we observed significant upregulation of miR-19a in osteosarcoma patients' tumor tissues as well as the osteosarcoma cell lines in vitro. We showed that knockdown of miR-19a by its antisense oligonucleotide (anti-miR-19a) significantly decreased the population of cancer stem cells in osteosarcoma cell lines. Furthermore, we found the miR-19a regulated the cell proliferation, migration, and viability in the human osteosarcoma–cancer stem cells. The gene of phosphatase and tensin homolog deleted on chromosome 10, which is an important tumor suppressor, was found to be directly regulated by miR-19a in human osteosarcoma–cancer stem cells. We demonstrated that knockdown of miR-19a increased the expression of phosphatase and tensin homolog deleted on chromosome 10. As the anti-miR-19a inhibited the phosphatidylinositol 3-kinase/AKT pathway and induced apoptosis of human osteosarcoma–cancer stem cells, the phosphatase and tensin homolog deleted on chromosome 10 small interfering RNA inhibited the effect of it. Meanwhile, the phosphatase and tensin homolog deleted on chromosome 10 small interfering RNA also abolished the effect of anti-miR-19a on inhibiting the cell proliferation, migration, and viability in the human osteosarcoma–cancer stem cells. In conclusion, our findings demonstrated that dysregulation of miR-19a plays critical roles in the osteosarcoma stem cells, at least in part via targeting the phosphatase and tensin homolog deleted on chromosome 10. Knockdown of miR-19a may represent a potential strategy for the osteosarcoma treatment.